2015
DOI: 10.1055/s-0034-1378867
|View full text |Cite
|
Sign up to set email alerts
|

Chromatography-Free and Eco-Friendly Synthesis of Aryl Tosylates and Mesylates

Abstract: Ar OHAr OTs TsCl, 15% NaOH or 10% K 2 CO 3 THF-H 2 O, 0 °C to r.t., 2 h Ar OMs MsCl, Et 3 N · chromatography-free · non-halogenated solvents · open to air · short reaction time · broad range of substrates · good to excellent yields · 43 examples EtOAc, 0 °C to r.t., 10 min Abstract Two chromatography-free and eco-friendly protocols have been developed to synthesize aryl tosylates and mesylates by the tosylation and mesylation of the corresponding hydroxyarenes, respectively. These protocols are superior to oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 10 publications
3
23
0
Order By: Relevance
“…17 The pivalates, tosylates, mesylates and carbamates were prepared using literature procedures. 18 2-Fluoro-4-methoxy benzaldehyde, and 2-fluoro-5-methyl benzaldehyde were obtained from Matrix Scientific and used as received. 2-Fluoro-5-(trifluoromethyl) benzaldehyde was obtained from Alfa Aesar and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…17 The pivalates, tosylates, mesylates and carbamates were prepared using literature procedures. 18 2-Fluoro-4-methoxy benzaldehyde, and 2-fluoro-5-methyl benzaldehyde were obtained from Matrix Scientific and used as received. 2-Fluoro-5-(trifluoromethyl) benzaldehyde was obtained from Alfa Aesar and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…Concluding the library of synthesized compounds, sulfonate esters TS18-TS20 (yields 52-90%) and glycosides TS21 (yield 34%) and TS22 (yield 35%) were accomplished by adopting the protocols of Lei et al, 38 Conchie et al, 39 and Zhu et al, 40 respectively. Two bands at 1364-1348 and 1179-1171 cm -1 for each sulfonate ester refer to S=O stretch of the functional group.…”
Section: Chemistrymentioning
confidence: 99%
“…In 2008, Gooßen's group [41] reported the first decarboxylative coupling of cinnamic acid with 1-chloro-4-methylbenzene. [49][50][51][52] Based on our efforts in transition metal-catalyzed cross-coupling research and considering our further interest in exploring the new-type synthetic methodology towards cross-coupling, [53][54][55][56][57] herein we report a successful attempt for the synthesis of stilbenes using C-O electrophiles by decarboxylative coupling using a combination of PdCl 2 (dppf) and CuCl 2 in DMI (1,3-dimethylimidazolidinone) under mild conditions (Scheme 1, equation (7)). Wu et al [36] then reported the efficient decarboxylation of cinnamic acid with aryl iodide catalyzed by a combination of palladium chloride and CyJohnPhos in the presence of Ag 2 CO 3 as an additive with good functional-group tolerance (Scheme 1, equation (4)).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, aryl tosylates are easy to handle because of their high hydrolytic stability and crystallinity. [49][50][51][52] Based on our efforts in transition metal-catalyzed cross-coupling research and considering our further interest in exploring the new-type synthetic methodology towards cross-coupling, [53][54][55][56][57] herein we report a successful attempt for the synthesis of stilbenes using C-O electrophiles by decarboxylative coupling using a combination of PdCl 2 (dppf) and CuCl 2 in DMI (1,3-dimethylimidazolidinone) under mild conditions (Scheme 1, equation (7)).…”
Section: Introductionmentioning
confidence: 99%